Pemanfaatan Pelepah Kelapa Sawit (Elaeis guenensisjacq. ) Sebagai Bahan Baku Pembuatan Briket Arang - Muhammad Yusuf; Rudianda Sulaeman; Evi Sribudiani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Midribof palm oilis one of thewasteoil palm plantationthat have notbeen used.Midrib of the coconut palm has a huge potential to be used as raw material for the manufacture of charcoal briquettes. Midrib of palm oil will be processed more intensively so that would be expected to reduce petroleum consumption. Charcoal is a porous solids containing 85-95% carbon produced from materials containing carbon by heating at high temperature. Utilization ofmidrib of palm oilasthe manufacture ofcharcoalbriquettescanbe usedtoreplaceconventionalfuelsscarceinits availabilityin nature, so thecharcoalbriquetteswithpalmmidribrawmaterialscanbe usedas analternative fuel.Makingcharcoalstartingfrompreparation of raw materials, carbonization, size reduction, mixingwithadhesive, printing, drying, andtesting, withthreedifferent treatments arethe treatmentsof charcoalwithnonsieveflour, flourtreatmentpulverizedcharcoalwith50meshsieve, andcharcoalpowdertreatmentsmoothedwith a70meshsieve. Tests oncharcoalbriquettesreferto theSNI. Keywords: Midrib of oil palm, Charcoal briquettes, treatment, SNI.